Sweet Taste Threshold among Medical Students with Family History of Diabetes Mellitus - Nasya Aisah Latif; Yulia Sofiatin; Maya Kusumawati; Rully Marsis Amirullah Roesli (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Diabetic patients have low sensitivity towards sweet taste, thus consuming more sugar. A young adult with family history of diabetes mellitus (FHD) who lives with diabetic parents may have an increased risk of overconsumption of sugar due to a similar dietary pattern, leading to diabetes. This study aimed to explore the difference in the sweet taste threshold (STT) between students with and without a family history of diabetes mellitus.Methods: This cross-sectional study was conducted in October –November 2018 on Class 2018 medical students living in a student dormitory who were divided into those with family history of diabetes (FHD) and those without it (non-FHD). Family history of diabetes and other known diseases were self-reported. The three-Ascending Forced Choice method was used to determine the sweet recognition threshold. Mann-Whitney analysis was used to compare the sweet taste thresholds between the two groups.Result: A total of 183 subjects participated in this study. The non-FHD group had a higher rank of sweet taste threshold than subjects in the FHD group (94.21 vs 81.16), albeit insignificant (p=0.192). Interestingly, the modes of best estimation threshold (BET) for non-FHD group was than the FHD group (0.067 M vs 0.043 M).Conclusion: The BET for students without family history of diabetes is higher than those with family history of diabetes. It is imperative that low sugar consumption campaign should also aim young people without FHD.